2016
DOI: 10.1002/2016jc011826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of current speed on mass flux to a model flexible seagrass blade

Abstract: Seagrass and other freshwater macrophytes can acquire nutrients from surrounding water through their blades. This flux may depend on the current speed (U), which can influence both the posture of flexible blades (reconfiguration) and the thickness of the flux‐limiting diffusive layer. The impact of current speed (U) on mass flux to flexible blades of model seagrass was studied through a combination of laboratory flume experiments, numerical modeling and theory. Model seagrass blades were constructed from low‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The former inequality is a good approximation for slender vegetation with b/H 1. The latter inequality holds whenever the velocity of the fluid is small compared to the speed of sound through the beams, which is also typical for aquatic vegetation (Lei & Nepf 2016).…”
Section: Simplification and Non-dimensionalisationmentioning
confidence: 86%
“…The former inequality is a good approximation for slender vegetation with b/H 1. The latter inequality holds whenever the velocity of the fluid is small compared to the speed of sound through the beams, which is also typical for aquatic vegetation (Lei & Nepf 2016).…”
Section: Simplification and Non-dimensionalisationmentioning
confidence: 86%
“…Previous studies have suggested that Turbulent KE may influence nutrient uptake (Anderson and Charters ; Koch ), and the total energy parameter captures this influence. Specifically, when Turbulent KE is weak, flux is controlled by the time‐mean diffusive sublayer thickness, which is a function of the time‐mean velocity (e.g., Hansen et al ; Rominger and Nepf ; Lei and Nepf ). However, when the Turbulent KE is high, periodic disturbances of the diffusive sublayer by the turbulence can create instantaneously higher concentration gradients at the surface and, thus, higher flux (e.g., Stevens and Hurd ; Huang et al ; Rominger and Nepf ).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic response of blades to symmetric wave forcing is investigated using the cable model. Blade geometric and material properties are adopted from those summarized in Lei and Nepf (), which are also provided in Table . In this case study, the blade length l=0.05–0.60 m and the flexural rigidity EI=0.13×105 to 3.9 ×105 N m 2 are used to represent a variety of blade characteristics.…”
Section: Symmetric and Asymmetric Blade Motionsmentioning
confidence: 99%
“…Blade Geometric and Material Properties for the Selected Species Used in the Present Study FollowingLei and Nepf (2016) …”
mentioning
confidence: 99%